Penggunaan Media Video Animasi dalam Pembelajaran Manasik Haji di PAUD Mawar (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
Learning Islamic education at PAUD Mawar often experiences various problems. This is caused by the inappropriate use of learning media, which causes a lack of student interest in learning participating. One of the learning materials that is not very interesting is Hajj. Using technology can be a solution for teachers in using interesting learning media to help students achieve learning goals. This research aims to describe how teachers use animated video media in teaching Hajj to students at PAUD Mawar and to find out the supporting and inhibiting factors for using animated video media. This research uses a qualitative method with a case study approach. Theetchniques of data collecting were carried out using interviews, observation and documentation. The results of the research show that the use of animated video media in learning Hajj for students at PAUD Mawar is effective because it helps students in learning, if animated video media is used with the right steps it can help make it easier for students to achieve learning goals.
Keywords: Using Learning Media; Animation Video Media; PAUD Mawar